VECTORS AND OPERATIONS ON THEM (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article discusses the concept of vectors, their types, and the basic mathematical operations performed on vectors.